Evaporation of pure and binary droplets on curved substrates. (1st November 2022) - Gurrala, Pradeep; Balusamy, Saravanan; Banerjee, Sayak; Sahu, Kirti Chandra
Highlights: The evaporation of pure ethanol and ethanol-water binary sessile droplets on one-dimensional cylindrical substrates is investigated. We demonstrate that pure ethanol has a greater spread and a smaller contact angle on curved substrates, whereas binary droplets exhibit a smaller spread on the curved substrates. Pure ethanol droplet does not preserve a spherical cap profile on the curved substrate, whereas a binary mixture does. The droplet perimeter remains constant on flat and curved substrates, resulting in identical evaporation times. Graphical abstract: Abstract: We investigate the evaporation of pure ethanol, water and ethanol-water binary sessile droplets on one-dimensional cylindrical substrates using shadowgraphy and infrared imaging techniques. Our results demonstrate that pure ethanol has a greater spread and a smaller contact angle on curved substrates, whereas pure water and binary droplets exhibit a smaller spread on the curved substrates. The top views of the droplet taken using the infrared imaging system demonstrate that a pure ethanol droplet does not preserve a spherical cap profile on the curved substrate, whereas a binary mixture does, which explains the difference in wetting dynamics on curved and flat substrates. Moreover, three-dimensional solid modelling is conducted to obtain the evolution of the morphology of the pure and binary droplets during evaporation. For all binary compositions, we observe that the droplet perimeter remains constant on flat and curved substrates, resulting in identical overall evaporation times on flat and curved substrates.